Buddhism and transgression: the appropriation of Buddhism in the contemporary West - Konik, Adrian (Studies in the history of religions, 2009)
Cover13; -- CONTENTS -- Foreword -- Preface -- Acknowledgments -- List of illustrations -- List of abbreviations -- Introduction -- PART I THE EMERGENCE OF DISCIPLINARY/BIO-POWER AND THE ARISING OF DISCURSIVE TENSION IN WESTERN SOCIETY -- Chapter One The problem of effective critique -- Chapter Two Disciplinary/bio-power and rational autonomy -- Chapter Three Secularized/medicalized confession and the problematization of rational autonomy -- PART II A REAPPRAISAL OF WESTERN INTEREST IN TIBET AND VAJRAY256;NA BUDDHISM -- Chapter Four The blank canvas of Tibet -- Chapter Five Lobsang Rampa's The Third Eye: The Autobiography of a Tibetan Lama -- Chapter Six John Blofeld's The Wheel of Life: The Autobiography of a Western Buddhist -- Chapter Seven Anagarika Govinda's autobiographical The Way of the White Clouds -- PART III ENGAGING WITH THE DISCURSIVE LIMITS OF TRANSGRESSION -- Chapter Eight The 'technological mind, ' discourse analysis, and the emergence of a new type of socially engaged contemporary Western Buddhism -- Conclusion -- Afterword -- Bibliography -- Index.